(untitled) (Bangladesh Journal of Pharmacology, 2013)
Eriocalyxin B (EriB) has been shown to possess promising anticancer potential against various cancer cells. However, its effect against bladder cancer cells remained unexplored. In this study, for the first time, we investigated the effects of EriB on cell proliferation, cell cycle, and apoptosis in bladder cancer T24 cells. In order to examine the effects of EriB on cell proliferation, cell cycle, and apoptosis, we performed MTT assay, flow cytometric analysis and western blot. The results revealed that EriB decreased the cell viability of T24 cells. Flow cytometric analysis demonstrated that EriB markedly induced apoptosis of T24 cells and arrested cell cycle at G2/M phase in a dose-dependent manner. Further characterization showed that EriB involved in the down-regulation of Bcl-2 and activation of caspase-3 before culminating in apoptosis in EriB-treated T24 cells. These in vitro results suggested that EriB should be further examined for in vivo activity in human bladder cancer.